1987
DOI: 10.1111/j.1471-0528.1987.tb03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour, birthweight and perinatal mortality by day of the week

Abstract: There were 46 974 births at the three largest Dublin maternity hospitals in the years 1980-1982. Data on numbers of spontaneous and elective births, birthweight and perinatal mortality were analysed by day of the week. Perinatal mortality rates were highest on Wednesdays and Saturdays. The rate on Sunday was close to average. The largest number of perinatal deaths per day occurred on Wednesdays and the smallest on Sundays. Significant variations in mortality rates and percentage low birthweight were found amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
1
15
1
Order By: Relevance
“…24 Although earlier neonatal studies noted higher weekend mortality rates, those analyses likely did not adjust adequately for potential confounders. 4,[6][7][8] Interestingly, the lack of a weekend effect in the current study and the recent neonatal study 24 differs from the results observed by Bell and Redelmeier, 1 who evaluated mortality rates among adult emergency admissions between 1988 and 1997 in Ontario, Canada. The difference between these findings may represent differences between adult and pediatric patient populations or a distinction between the structure or processes of health care for adult versus pediatric patients.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…24 Although earlier neonatal studies noted higher weekend mortality rates, those analyses likely did not adjust adequately for potential confounders. 4,[6][7][8] Interestingly, the lack of a weekend effect in the current study and the recent neonatal study 24 differs from the results observed by Bell and Redelmeier, 1 who evaluated mortality rates among adult emergency admissions between 1988 and 1997 in Ontario, Canada. The difference between these findings may represent differences between adult and pediatric patient populations or a distinction between the structure or processes of health care for adult versus pediatric patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, neonatal mortality rates were shown to be slightly higher among infants born on weekends and during evening hours, compared with those born on weekdays and during daytime hours, respectively. [3][4][5][6][7][8] Whether an association exists between patient outcomes and time of admission in the pediatric patient population is unknown.To address this question, the Pediatric Intensive Care Unit Evaluations (PICUEs) database, representing a cohort of 34 993 pediatric ICU (PICU) patients from 15 institutions in the United States, was analyzed. 9 The objectives of this study were to compare the risk-adjusted mortality rates for weekend admissions versus weekday admissions and the risk-adjusted mortality rates for evening admissions versus daytime admissions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies specifically comparing weekends to weekdays suggest no differences in neonatal death rates (57). Aside from neonatal mortality, there is little evidence regarding rates of other serious adverse outcomes during weekends compared to weekdays, despite their potentially profound impacts on women and infants.…”
Section: Introductionmentioning
confidence: 99%
“…14 A spate of studies has analyzed the question of whether weekend births are more dangerous (see for example MacFarlane, 1978;1979;Mangold, 1981;Hendry, 1981;Mathers, 1983;Dowding et al, 1987;Gould et al, 2003;Luo et al, 2004;Hong et al, 2007). The majority of these papers find that while the infant mortality rate is higher on weekends, this does not necessarily mean that it is more dangerous for a given child to be born on a weekend.…”
Section: Inauspicious Daysmentioning
confidence: 99%